2023
DOI: 10.1101/2023.03.07.531415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structurally divergent and recurrently mutated regions of primate genomes

Abstract: To better understand the pattern of primate genome structural variation, we sequenced and assembled using multiple long-read sequencing technologies the genomes of eight nonhuman primate species, including New World monkeys (owl monkey and marmoset), Old World monkey (macaque), Asian apes (orangutan and gibbon), and African ape lineages (gorilla, bonobo, and chimpanzee). Compared to the human genome, we identified 1,338,997 lineage-specific fixed structural variants (SVs) disrupting 1,561 protein-coding genes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…We found that the L1PA2 insertion site is present-and identical-in human, chimpanzee, bonobo, and gorilla, but not in orangutan, macaque, or other lower species (Fig. 5F) (49). Thus, this L1PA2 insertion can be estimated to have occurred around 10 to 20 million years ago.…”
Section: L1-lncrna Linc01876 Is a Human-specific Transcriptmentioning
confidence: 83%
See 1 more Smart Citation
“…We found that the L1PA2 insertion site is present-and identical-in human, chimpanzee, bonobo, and gorilla, but not in orangutan, macaque, or other lower species (Fig. 5F) (49). Thus, this L1PA2 insertion can be estimated to have occurred around 10 to 20 million years ago.…”
Section: L1-lncrna Linc01876 Is a Human-specific Transcriptmentioning
confidence: 83%
“…Denisova and Neanderthal genomes both displayed the human variant, suggesting that the nucleotide change occurred before the split of archaic human species (Fig. 5F) (49). This analysis indicated that it is possible that the L1-lncRNA promoter may be silenced by DNA methylation or other repressive factors in nonhuman primates due to the expression and translation of an ORF0-fusion-transcript.…”
Section: L1-lncrna Linc01876 Is a Human-specific Transcriptmentioning
confidence: 88%
“…Besides humans, only gibbons, orangutans, gorillas, bonobos, and chimpanzees encode for RGPDs . There is no evidence of RGPD ‐like genes in any other primate or mammal [77]. Each ape species encodes for a different set of RGPD genes: one copy in gibbons, three in orangutans, four in gorillas, six in chimpanzees, and seven in humans (i.e., RGPD1‐8 without any RGPD7).…”
Section: Evolution Of Ranbp2mentioning
confidence: 99%
“…Each ape species encodes for a different set of RGPD genes: one copy in gibbons, three in orangutans, four in gorillas, six in chimpanzees, and seven in humans (i.e., RGPD1‐8 without any RGPD7). Strikingly, a recent study revealed that the multiple copies of RGPD arose mostly independently in the five different ape lineages, which constitutes an extreme example of homoplasy [77]. Only RGPD2 in African great apes (gorillas, chimpanzees, and humans) appears syntenic and orthologous.…”
Section: Evolution Of Ranbp2mentioning
confidence: 99%
See 1 more Smart Citation